Património industrial dos antigos coutos de Alcobaça - Maduro, António (2016)
The monastic industrial complex, which is inseparable from the agrarian architecture and from the agricultural distribution of the fruits of the Earth, was supremely represented in the granges and farms directly explored by the monastery or given as a privilege. This way, they kept the products of their own cultivation or the ones of the given privileges according to the manorial economy, the olives were changed into olive oil, the grapes into wine and cereals into flour. The creation of industrial units, besides paying attention to the geographic proximity of the agricultural exploration and the easy control made by the institution which owned the right of monopoly, equally considered the energy criterion which implied a correct use of the waterlines that furrowed the territory. The advantage of the hydraulic engine, explains that the “Alcoa” river, the only permanent watercourse, received the most important industrial settlements. However, not all industrial units could benefit from the water force, namely the oil-presses attached to the olive groves which adorn the moorland mountain and whose motive force depended on cattle yoke. Between the last years of the 19th century and the first decades of the 20th century, this industrial heritage was abandoned and destroyed due to the natural technological obsolescence, or to the occupation of its place by other industries. Our communication aims to analyze some of this patrimony, which proceeds from the industrial archeology together with the agrarian fields used as a reference. Moreover, we want to promote the interest to visit this threatened heritage, highlight it and, eventually, contribute to its further qualification.